Neonates with culture proven sepsis have lower amounts and percentage of CD45RA+t cells - Aygun, A. Denizmen; Kurt, A. Nese Citak; Godekmerdan, Ahmet; Kurt, Abdullah; Akarsu, Saadet; Gurgoze, M. Kaya; Yilmaz, Erdal (Springer/Plenum Publishers, 2008)
To evaluate the expression of lymphocyte subsets in newborns diagnosed as culture proven or culture negative sepsis and to investigate the differentiation. The aim of this study is to explore neonatal immunology in newborns diagnosed as culture proven or culture negative neonatal sepsis and to identify their place in the diagnosis. This prospective study was performed in newborns who were diagnosed as neonatal sepsis and hospitalized in a tertiary care hospital and who were classified as culture proven sepsis (n=12), as culture negative sepsis (n=21) and healthy (n=17). Lymphocyte subsets were obtained at time of diagnosis. Culture proven sepsis had statistically significant increase of WBC compared to culture negative sepsis and control groups (p < 0.05). Significant decreases were observed of percentage of lymphocyte, when compared to culture negative sepsis and control group (p < 0.05). Percentage of CD4(+) stop was lower in culture proven sepsis and absolute count of CD4(+) stop was lower in culture negative sepsis (p < 0.05). Percentage and absolute count of CD45RA(+) stop were lower in culture negative sepsis than control and percentage of CD45RA(+) stop was lower in culture proven sepsis than control (p < 0.05). Percentage of CD45RO(+) stop was higher in culture proven sepsis than control group (p < 0.05). It is clear that during neonatal sepsis lymphocyte subsets are different from healthy controls. Whether the described abnormalities represent the absence of a normal maturation process, rather, pathological events is still not clear.
Keywords: newborn; sepsis; flow cytometry; lymphocyte subsets